"Playing a Game of Worlds": Postmodern Time and the Search for Individual Autonomy in Vladimir Nabokov's Pale Fire - Jill LeRoy-Frazier (Studies in 20th & 21st Century Literature, 2003)
This article enters the ongoing critical debate surrounding Pale Fire, as to whether the apparent structure of the novel can be taken at face value. Do the central characters, John Shade and Charles Kinbote, constitute separate voices within the novel, as poet and commentator respectively, or is one in fact the fictional creation of the other? Arguing that the dispute arises out of a set of critical assumptions that negate at least some of the possible implications of Nabokov's own views of art's purpose and function, the essay asserts that Nabokov's disbelief in objective reality renders the entire Shade/Kinbote debate irrelevant. By focusing upon the consequent challenges presented by radical subjectivity and linguistic indeterminacy in an always-fictional world, the essay suggests that Nabokov's art, rather than being diminished by an exploration of its relationships to post-structuralism, is in fact reaffirmed as a transcendent act of the human spirit.
Keywords: Pale Fire; autonomy; postmodern; postmodern time; individual autonomy; Vladimir Nabokov; John Shade; Charles Kinbote; voice; commentator; poet; art' s purpose; art' s function; art; objective reality; reality; fictional world; post-structuralism; human spirit; transcendent